2017
DOI: 10.1093/geroni/igx004.3497
|View full text |Cite
|
Sign up to set email alerts
|

Use of Telehealth During Physical Rehabilitation for Patients With Chf: A Systematic Review

Abstract: (colorful, memorable cues placed at key decision points) cue conditions. The results showed that there was a significant interaction among group, day, and trial (F (8, 987) = 8.049; p < .0001 indicating that the subjects in the control group found their way faster over days and trials in both cue conditions when compared to the AD/MCI group. The control group found the goal significantly more often (M = 16.1, SD = 2.23) than the AD/MCI group (M = 6.45, SD = 5.43); t (68) = 25.806, p < .001. There was an intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] Prior to the COVID-19 pandemic, the practice of telehealth was shown to be cost-effective, especially in the treatment of chronic diseases like diabetes mellitus and obesity. [10][11][12][13][14] With the emphasis on remote care during the COVID-19 pandemic, many practices and hospitals produced policy changes to apply telehealth in both medical and surgical fields. 15 Unfortunately, the field of otolaryngology has many unique challenges when migrating to telehealth, especially given the importance of physical exams as well as the frequent use of endoscopy and microscopy during complete head and neck evaluations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9] Prior to the COVID-19 pandemic, the practice of telehealth was shown to be cost-effective, especially in the treatment of chronic diseases like diabetes mellitus and obesity. [10][11][12][13][14] With the emphasis on remote care during the COVID-19 pandemic, many practices and hospitals produced policy changes to apply telehealth in both medical and surgical fields. 15 Unfortunately, the field of otolaryngology has many unique challenges when migrating to telehealth, especially given the importance of physical exams as well as the frequent use of endoscopy and microscopy during complete head and neck evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…1-9 Prior to the COVID-19 pandemic, the practice of telehealth was shown to be cost-effective, especially in the treatment of chronic diseases like diabetes mellitus and obesity. 10-14 With the emphasis on remote care during the COVID-19 pandemic, many practices and hospitals produced policy changes to apply telehealth in both medical and surgical fields. 15…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Previous studies demonstrated telehealth to be cost-effective and useful. [10][11][12][13][14] Given the perceived utility of remote care under these circumstances, policy changes have readily promoted its increased use across specialties. 15 Implementing telehealth on a wide scale presents unique challenges to otolaryngologists given routine use of endoscopy and microscopy.…”
mentioning
confidence: 99%
“…With the coronavirus disease 2019 (COVID‐19) pandemic, otolaryngologists, among other specialties, implemented telehealth strategies to adapt to physical distancing guidelines 1–9 . Previous studies demonstrated telehealth to be cost‐effective and useful 10–14 . Given the perceived utility of remote care under these circumstances, policy changes have readily promoted its increased use across specialties 15…”
mentioning
confidence: 99%